Alcohol and Breast Cancer: Results From the Women's Wellness After Cancer Program Randomized Controlled Trial. Issue 2 (20th March 2022) - Balaam, Sarah; Bailey, Tom G.; Anderson, Debra; Retell, James; McCarthy, Alexandra L.
Abstract : Background: There is evidence that drinking alcohol increases the risk of recurrent breast cancer. It is unclear whether Australian women with breast cancer are aware of this evidence or modify their alcohol intake accordingly. Objective: This article reports a secondary analysis of data from the Women's Wellness after Cancer Program (WWACP) randomized controlled trial (N = 351). The WWACP aimed to enhance quality of life and reduce chronic disease risk in women previously treated for cancer through lifestyle modification. Here we provide the alcohol-related data from the study's breast cancer participants (n = 269). We analyzed baseline alcohol consumption, the variables associated with alcohol intake, and intervention effect on intake at weeks 12 (end of intervention) and 24 (to determine sustainability). Interventions/Methods: Measures included the Dietary Questionnaire for Epidemiological Studies, Short Form-36, International Physical Activity Questionnaire, Green Climacteric Scale, Pittsburgh Sleep Quality Index, and Center for Epidemiologic Studies Depression Scale. Results: Most participants practiced safe alcohol consumption. Among drinkers, drinking caffeine, smoking, emotional and physical role limitations, and greater discomfort with vasomotor symptoms were associated with increased intake. Relative to baseline, alcohol consumption decreased from 5.22 g/d to 4.18 g/d in the intervention group, whereas consumption increased among control subjects at 12 weeks. No difference between groups was observed at week 24. Conclusion: The intervention was associated with less alcohol intake at week 12 among drinkers, but this reduction was not sustained at the 24-week follow-up. Implications for Practice: Future iterations of the WWACP will emphasize stronger messaging and supports regarding alcohol consumption after breast cancer treatment.